2019
DOI: 10.3389/fpsyt.2019.00810
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Sertraline in Young Children With Autism Spectrum Disorder

Abstract: Objective: Selective serotonin reuptake inhibitors like sertraline have been shown in observational studies and anecdotal reports to improve language development in young children with fragile X syndrome (FXS). A previous controlled trial of sertraline in young children with FXS found significant improvement in expressive language development as measured by the Mullen Scales of Early Learning (MSEL) among those with comorbid autism spectrum disorder (ASD) in post hoc analysis, prompting the authors to probe wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…We did not find an effect of trial duration, yet shorter-term trials have been associated with larger placebo response in psychiatry [ 50 ]. However, in longer-term trials including young children, anticipated developmental trajectories could also explain placebo effects and subsequently mask drug-placebo differences [ 101 ]. Therefore, developmentally based scales might be necessary to overcome this challenge [ 82 ] as well as trial designs could include additional follow-up assessments in order to confirm stability of improvement [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find an effect of trial duration, yet shorter-term trials have been associated with larger placebo response in psychiatry [ 50 ]. However, in longer-term trials including young children, anticipated developmental trajectories could also explain placebo effects and subsequently mask drug-placebo differences [ 101 ]. Therefore, developmentally based scales might be necessary to overcome this challenge [ 82 ] as well as trial designs could include additional follow-up assessments in order to confirm stability of improvement [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The amount that was used at each 3 months visit was measured to document compliance. More details are described in Potter et al (2019). Biological samples collected at baseline and post-treatment were approved by the UC Davis Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, evidence suggests that sertraline could be useful in young children with ASD since the serotonergic system is disrupted in early development of ASD children. Based on these findings, a 6-month randomized, placebo-controlled, doubleblind clinical trial of low-dose sertraline in children ages 39-71 months old with ASD was conducted at the UC Davis MIND Institute to evaluate the efficacy and benefit with respect to early expressive and receptive language development and global clinical improvement (Potter et al, 2019). In the present study, we further investigated the participants to identify molecular biomarkers predictive of efficacy and responsiveness to sertraline treatment in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Ghanbari et al (2011) in their research on irainian children showed that ubscales of PAS had moderate to high internal consistency and good reliabiity. Validity evaluations also yielded positive results (29) The PAS has previously been employed and indicated to be a valid measure of anxiety levels in preschoolers with ASD (30,31). The score of obsessive-compulsive subscale was not included, because children with ASD serve this behavior for self-soothing or regulation of emotions (32) and it is not related to anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation is that lack of psychometric characteristics for the ASD preschoolers of the PAZ may lead to an unreliable evaluation of anxiety. However, this scale has previously been used to measure anxiety in preschoolers with ASD and indicated to be a valid measure of anxiety levels in this population (30,31).…”
Section: Limitationmentioning
confidence: 99%